Recuperación de solventes de una empresa del sector flexográfico (2017)
In this work, the sampling and characterization of liquid print residues generated by a flexographic company were carried out. The research used the method described by the NTC 619 to determine the distillation curve and to establish the composition of the distillate of nine fractions; subsequently, using a differential distillation model with the arrangement of finite differences, the instantaneous structures of bottoms were calculated. With the use of the Aspen Plus program, it calculated the bubble temperatures under two thermodynamic models, in which it found significant differences with the experimental data. It also elaborated the residual curve maps for the standard compositions of the three-major volatile organic compounds of the mixture, which reported a right prediction of the structure of bottoms with the UNIQUAC and NRTL models, against the data obtained experimentally.